Respuesta :

First of all observe that

[tex]r^6s^3=(r^2s)^3 \implies \sqrt[3]{r^6s^3}=\sqrt[3]{(r^2s)^3}=r^2s[/tex]

So, we have

[tex]\log(r^5s^6\sqrt[3]{r^6s^3})=\log(r^5s^6\cdot r^2s)[/tex]

We can simplify the input as

[tex]\log(r^5s^6\cdot r^2s)=\log(r^7s^7)[/tex]

The logarithm of a multiplication is the sum of the logarithms:

[tex]\log(r^7s^7)=\log(r^7)+\log(s^7)[/tex]

Finally, invoke the logarithm property [tex]\log(a^b)=b\log(a)[/tex]

to get the final answer

[tex]\log(r^7)+\log(s^7)=7\log(r)+7\log(s)[/tex]